How is organisational fit addressed in Australian entry level midwifery job advertisements - Dianne Bloxsome; Courtney Glass; Sara Bayes (BMC, 2021)
Abstract Background Midwifery job retention is an ongoing global issue. Prior research has recognised that considering an individual's attributes in relation to their work environment may assist in improving job satisfaction among midwives, leading to improved long-term job retention in the midwifery profession. The aim of this study was to evaluate whether, and how organisational fit is addressed in current entry level midwifery job advertisements within Australia. Methods Midwifery jobs were searched for within 12 search engines, using the search term 'midwife', including Seek.com , Indeed.com , government employment websites for all Australian states and territories, and private health organisation websites. Data were extracted from eligible job advertisements by three independent researchers. Extracted data encompassed elements addressing person-job fit and person-organisation fit. Content analysis involving chi-square and Fischer exact tests were completed on extracted data. Results Key findings demonstrate private health care organisations (29.2%) are more likely than public health care organisations (8.8%) to ask potential candidates to have additional qualifications, however, public health care organisations (34.1% vs. 16.7%) are more likely to ask for dual registration as a midwife and nurse. This is further supported by private health care organisations being more likely to refer to the candidate as a midwife (72.9% vs. 48.4%) than as a nurse. Private health care organisations more often noted access to support for employees and were more likely to mention access to employee assistance programs (41.7% vs. 13.2%), orientations (16.7% vs. 0%) and included benefits (72.9% vs. 42.9%). Clinical skills and personality traits were more frequently addressed in public health organisation advertisements; these included a requirement of employees to be accountable (49.5% vs. 6.3%), innovative (28.6% vs. 0%), have teamwork (69.2% vs. 52.1%) and conflict resolution skills (36.3% vs. 8.3%), and have knowledge of legislation (44.0% vs. 25.0%) and contemporary midwifery issues (28.6% vs. 4.2%). Conclusion This study highlights that organisations employing midwives may be unwittingly contributing to the problem of midwife attrition through inattention to factors that endear midwives to workplaces in job advertisements. Further work developing employee selection and recruitment processes that are informed by the concept of person-job-organisation fit, is necessary.